Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1046/j.1365-2621.2002.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity of brown algal phlorotannins against hyaluronidase

Abstract: The inhibitory effect of brown algal phlorotannins on hyaluronidase was evaluated by an in vitro assay. Crude phlorotannins from the brown algae Eisenia bicyclis and Ecklonia kurome had a stronger inhibitory effect than well-known inhibitors such as catechins and sodium cromoglycate. IC 50 values of the following six phlorotannins: phloroglucinol, an unknown tetramer, eckol (a trimer), phlorofucofuroeckol A (a pentamer), dieckol and 8,8¢bieckol (hexamers), were 280, 650, >800, 140, 120 and 40 lM, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
109
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(117 citation statements)
references
References 26 publications
3
109
0
1
Order By: Relevance
“…Although the strong effect of PFF-A corresponded to the results of Shibata et al (2002), this paper is the first to report the inhibitory effects of 6,8'-bieckol and PFF-B on hyaluronidase activity. Our previous study has shown that the inhibitory effect of the eckol on degranulation from rat basophile leukemia (RBL)-2H3 cells was the weakest compared to those of the other five phlorotannins (Sugiura et al, 2007).…”
Section: Inhibitory Effects Of the Six Phlorotannins On Hyaluronidasesupporting
confidence: 60%
See 2 more Smart Citations
“…Although the strong effect of PFF-A corresponded to the results of Shibata et al (2002), this paper is the first to report the inhibitory effects of 6,8'-bieckol and PFF-B on hyaluronidase activity. Our previous study has shown that the inhibitory effect of the eckol on degranulation from rat basophile leukemia (RBL)-2H3 cells was the weakest compared to those of the other five phlorotannins (Sugiura et al, 2007).…”
Section: Inhibitory Effects Of the Six Phlorotannins On Hyaluronidasesupporting
confidence: 60%
“…In this study, the inhibitory effect of the eckol on the hyaluronidase activity was also the weakest compared to those of the other five tested phlorotannins. When the phlorotannins from E. bicyclis were investigated for their hyaluronidase inhibitory activities, the activity of eckol was the weakest of all the tested phlorotannins (Shibata et al, 2002). As the molecular size of eckol is the smallest (372) of all the tested phlorotannins, the molecular size may be an important factor governing the inhibitory effects of the phlorotannins on the hyaluronidase activity and degranulation from RBL cells.…”
Section: Inhibitory Effects Of the Six Phlorotannins On Hyaluronidasementioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological activities observed include inhibition of a number of enzymes such as hyaluronidase, phospholipase A, lipoxygenase, cyclooxygenase-1, glycosidases, tyrosinase, HIV-1 reverse transcriptase and HIV-1 protease (e.g. Shibata et al, 2002a;Shibata et al, 2002b;Shibata et al, 2003;Ahn et al;, Kang et al, 2004b, antioxidative effects (e.g. Nakamura et al, 1996;Chkhikvishvili & Ramazanov, 2000;Jimenez-Escrig et al, 2001;Kang et al, 2004a) and antibacterial activity (Nagayama et al, 2002;Sandsdalen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…3) Phlorotannins have been reported to have certain biological activities, such as antioxidation, 4) bactericide, 5) anti-cancer, 6) anti-diabetic complications, 7,8) and chemoprevention against several vascular diseases. 9,10) Although some anti-inflammatory activities of phlorotannins have also been reported, 11,12) their inhibitory effect on histamine release from the stimulated cultured cells is still unknown.…”
mentioning
confidence: 99%